1988
DOI: 10.1148/radiology.168.1.3132732
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of helium-ion radiation therapy and split-course megavoltage irradiation for unresectable adenocarcinoma of the pancreas. Final report of a Northern California Oncology Group randomized prospective clinical trial.

Abstract: Forty-nine patients with locally advanced carcinoma of the pancreas were treated in a randomized, prospective study comparing definitive helium ion radiation therapy with conventional split-course megavoltage photon irradiation. Patients in each treatment arm underwent exploratory staging laparotomy followed by concurrent radiation therapy and 5-fluorouracil chemotherapy. Patients treated with photons received 6,000 cGy over a period of 10 weeks; patients treated with helium irradiation received a 6,000-7,000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 0 publications
0
55
0
1
Order By: Relevance
“…Early data from the University of California, Berkeley, comparing helium and photon irradiation in 49 patients reported superior LC rates for helium therapy, although increased LC did not translate into increased survival in this cohort [66]. Although the protocol applied combined chemoradiation, the treatment regimen consisted of a split-course radiation treatment, which would not be state of the art today.…”
Section: Review Of Clinical Experience With Ion Beam Radiotherapymentioning
confidence: 95%
See 2 more Smart Citations
“…Early data from the University of California, Berkeley, comparing helium and photon irradiation in 49 patients reported superior LC rates for helium therapy, although increased LC did not translate into increased survival in this cohort [66]. Although the protocol applied combined chemoradiation, the treatment regimen consisted of a split-course radiation treatment, which would not be state of the art today.…”
Section: Review Of Clinical Experience With Ion Beam Radiotherapymentioning
confidence: 95%
“…Further dose escalation, by the application of particle therapy, has been investigated in a number of studies. Kato and co-workers published two Phase I-II trials (involving 44 and 94 patients, respectively) on the treatment with carbon ions [66][67][68]. All patients were diagnosed with locally advanced carcinoma of the cervix (median diameter 6.5 cm).…”
Section: Carcinoma Of the Uterine Cervixmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The other compared PBT to transarterial chemoembolisation (TACE). 22 The reference list of the Lodge et al 20 and De Ruysscher et al 19 systematic reviews identified that only four of the combined 106 studies were RCTs, [24][25][26][27] with the rest mostly level IV evidence through retrospective Once repeated studies between systematic reviews were removed, nine RCTs remained. Only one of these compared PT to photon therapy in the context of prostate cancer dose escalation 25 using older (passive scattering) treatment delivery techniques and underdeveloped image guidance, the remaining were pure dose fractionation comparison studies, [28][29][30][31] examined Helium ion therapy 24,26 or compared PT to another form of treatment such as TACE 22 or transpupillary thermotherapy.…”
Section: Search Strategy Imentioning
confidence: 99%
“…Mimo znacznej liczby [119][120][121][122][123][124][125][126] dobrze zaplanowanych badań w małych grupach chorych przeprowadzanych w ciągu 30 lat rola radioterapii z zastosowaniem cytostatyków lub bez ich zastosowania nie została wystarczająco potwierdzona. Należy przypuszczać, że gdyby radioterapia miała istotne znaczenie w terapii raka trzustki, do tej pory znaleziono by na to dowody.…”
Section: Radioterapia Plus Lekiunclassified